2023
DOI: 10.3389/fendo.2023.1124405
|View full text |Cite
|
Sign up to set email alerts
|

Roles of endoplasmic reticulum stress in the pathophysiology of polycystic ovary syndrome

Abstract: Polycystic ovary syndrome (PCOS) is the most common endocrine disorder among reproductive-age women, affecting up to 15% of women in this group, and the most common cause of anovulatory infertility. Although its etiology remains unclear, recent research has revealed the critical role of endoplasmic reticulum (ER) stress in the pathophysiology of PCOS. ER stress is defined as a condition in which unfolded or misfolded proteins accumulate in the ER because of an imbalance in the demand for protein folding and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 112 publications
0
13
0
Order By: Relevance
“…Oxidative stress has been reported to enhance ovarian steroidogenic enzymes and increase androgen levels in women with PCOS (162). Endoplasmic reticular stress pathways are activated in the ovaries in mouse models and in humans, and may contribute to the pathophysiology of PCOS through multiple effects in granulosa cells (163,164). As discussed previously, AGE and RAGE have been found to cause altered steroidogenesis in granulosa cells in PCOS (99).…”
Section: Hyperandrogenism and Chronic Inflammationmentioning
confidence: 83%
“…Oxidative stress has been reported to enhance ovarian steroidogenic enzymes and increase androgen levels in women with PCOS (162). Endoplasmic reticular stress pathways are activated in the ovaries in mouse models and in humans, and may contribute to the pathophysiology of PCOS through multiple effects in granulosa cells (163,164). As discussed previously, AGE and RAGE have been found to cause altered steroidogenesis in granulosa cells in PCOS (99).…”
Section: Hyperandrogenism and Chronic Inflammationmentioning
confidence: 83%
“…The potential antitumor effects of cannabinoids through the Notch1 signaling pathway were previously demonstrated in glioma, where THC induced the expression of p8 protein, upstream to ATF3/4 ( 57 ). The activation of Notch signaling by ER stress was demonstrated in additional systems, including Alzheimer’s disease ( 58 ), polycystic ovary syndrome ( 59 ) and other types of cancer ( 60 , 61 ). A previous work that focused on chronic lymphocytic leukemia suggested a role for ER stress in Notch1 cleavage and leukemia cell death through the inhibition of proteasome activity ( 62 ).…”
Section: Discussionmentioning
confidence: 99%
“…Research has found that the relative expression of BIP mRNA and protein was signi cantly higher in the PCOS observation group than in the control group; similarly, the relative expression of CHOP mRNA and protein tended to be higher in the PCOS observation group than in the control group, although there was no signi cant difference [79]. The result several genes involved in UPR er and UPR mt were overexpressed in the GCs of PCOS-IR.…”
Section: Polycystic Ovary Syndromementioning
confidence: 94%